Transforming Leadership in MI Muhammadiyah Wangon of Banyumas Regency - Miladiyah, Isnawati (International Conference of Moslem Society, 2018)
This research described the Transformational Leadership in MI (Islamic Elementary School) Muhammadiyah Wangon of Banyumas Regency. The purpose of this research was to know, describe and analyze the efforts made by Head of Madrasah MI Muhammadiyah Wangon of Banyumas Regency by using transformational leadership theory from Bass model. The method used was descriptive analysis method. The data are presented by using sentences to obtain clear and detailed information. Meanwhile the data collection techniques used are: observation, interview, documentation and questionnaire. This research found that transformational leadership in MI Muhammadiyah Wangon Banyumas Regency is embodied in 4 I namely Idealized influence, Individualism consideration, Intellectual stimulation and Inspiration motivation. Idealized influence of the head of MI Muhammadiyah Wangon have an enormous influence for subordinates, thus giving rise to charismatics. Individualism consideration of the head of MI Muhammadiyah Wangon is shown in his high concern on the need for the development of his subordinates. Intellectual stimulation of the Head of MI Muhammadiyah Wangon is shown in his continuous providing scientific stimulation to the subordinates. Inspirational motivation of the head of MI Muhammadiyah Wangon is shown in his continuous giving inspiring motivation to his subordinates so that the next leaders will emerge. Leadership in Madrasah Ibtidaiyah can be obtained a model of transformational leadership if the principal Madrasah: 1) taqwa to Allah SWT, 2) havimg influence and being able to be confident, 3) appreciating achievements of his staff, 4) being able to communicate with various types of people, 5) (time, energy, mind, material), 6) Changing agent, 7) Mastering various management, 8) Competitive, 9) Giving authority, 10) Generating the next leader.